2021
DOI: 10.7759/cureus.18568
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Japanese Patients Who Visited a COVID-19 Aftercare Clinic for Post-Acute Sequelae of COVID-19/Long COVID

Abstract: The long-term clinical course, prognosis, and optimal management of symptoms and conditions after the acute phase of coronavirus disease 2019 remain to be elucidated. The purpose of this study was to clarify the characteristics of patients referred to a COVID-19 aftercare (CAC) clinic established at a tertiary academic hospital in Japan. MethodsThis study was a descriptive case series study. All patients who visited the CAC clinic between February 15 and September 17 in 2021 were included. Patients' backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
0
31
1
Order By: Relevance
“…In this study, we obtained information for patients with long COVID directly through medical interviews and by physical examinations at our CAC. Studies on long COVID in Europe, the United States, China and Japan, [ 21 , 26 ] as well as a meta-analysis have gradually revealed the clinical characteristics and prognosis of long COVID [ 13 , 27 ]. However, most of the information for those studies was obtained from online or telephone interviews and there was no follow-up of the patients in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we obtained information for patients with long COVID directly through medical interviews and by physical examinations at our CAC. Studies on long COVID in Europe, the United States, China and Japan, [ 21 , 26 ] as well as a meta-analysis have gradually revealed the clinical characteristics and prognosis of long COVID [ 13 , 27 ]. However, most of the information for those studies was obtained from online or telephone interviews and there was no follow-up of the patients in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for establishing the clinic were to provide treatment for patients suffering from long COVID and to analyze the clinical characteristics of patients with long COVID in order to establish treatment strategies. Our previous study revealed that (i) most patients with long COVID had not required hospitalization in the acute phase and (ii) general fatigue was a major complaint in more than half of the patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of iron or zinc can be a treatment option for treating the deficiency of these minerals [9]. Although hair loss is not life-threatening, it can considerably affect the patient's quality of life; hence, physicians need to provide complete care for such patients [4]. Furthermore, physicians need to reduce anxiety by explaining to patients their conditions, sharing medical information, and eliminating their psychophysical stress by managing various systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…One month following discharge, he developed noticeable hair loss and observed shower clogging by the fallen hair daily (Figure 1). Because the hair loss continued, the patient visited our COVID-19 aftercare clinic four months after the first onset of COVID-19 [4]. By the first visit, alopecia had spread gradually across the entire head (Figure 2).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation